Mapping the Impact: Property Crime Trends in Kuching, Sarawak, During and After the COVID-19 Period (2020-2022) - Ahmad, Azizul; Kelana, Muhammad Haziq; Soda, Ryoji; Jubit, Norita; Mohd Ali, Asykal Syakinah; Bismelah, Luqman Haqim; Masron, Tarmiji (Faculty of Geography, Universitas Gadjah Mada, 2024)
This study aims to explore how COVID-19 and the Movement Control Order (MCO) have influenced the trend of property crimes in Kuching, Sarawak spanning from 2020 until 2022. The lockdown imposed by the government had impacted daily activities in Malaysia, including those in Kuching, Sarawak. The methodology employed in this research involves descriptive analysis and spatial analysis, specifically using the Hot Spot Getis GI* technique, with the support of ArcGIS software. It examines relationships between crime and geography. The trend of property crime cases dropped from 1,144 cases (2020) to 813 cases in 2021 and ended with 683 cases in the year 2022. The value of GiZScore from the lowest of 2.066694 to the highest of 13.365677 is from the year 2021. Property crime in Kuching's urban center was targeted even during MCO beginning March 2020 to November 1, 2021. This indicates a notable decrease in property crime trends during the COVID-19 (2020-2021) pandemic period due to the MCO and lockdown which continue to impact into the subsequent endemic era of 2022. This demonstrates the efficiency of the Royal Malaysia Police, particularly in the context of Kuching, Sarawak.